Associations between polymorphisms of the ACYP2 gene and Liver cancer risk: A case‐control study and meta‐analysis. Issue 7 (23rd May 2019) - Zhao, Wenhui; Liu, Xu; Yu, Zhendong; Xiong, Zichao; Wu, Jiamin; Sun, Yao; Niu, Fanglin; Liu, Jikui; Jin, Tianbo
Abstract: Background: ACYP2 gene may be involved in the process of telomere shortening which may be involved in the liver cancer. So, this research was to examine whether the ACYP2 gene polymorphism has impact on the risk of liver cancer in Chinese population. Methods: Two hundred and fifty cirrhosis patients and 248 liver cancer patients were selected. Unconditional logistic regression was to calculate the odds ratio (OR) and 95% confidence intervals (CIs). Analyze the relationship between ACYP2 gene polymorphism and tumor using meta‐analysis. Analyze the expression of ACYP2 gene in liver cancer and its influence on the prognosis of liver cancer by databases (Ualcan, GTEX and Kaplan–Meier plotter). Results: In the allele model, ACYP2 rs843720 was protection against the occurrence of cirrhosis developed into liver cancer (OR = 0.76, 95% CI: 0.58–0.99, p  = 0.04). Rs1682111 and rs843720 play a protective role in the additive model (rs1682111: OR = 0.69, 95% CI: 0.52–0.93, p  = 0.01; rs843720: OR = 0.73, 95% CI: 0.54–0.98, p  = 0.04).While rs843645 G allele increased the risk of cirrhosis developed into liver cancer under the additive model (OR = 1.42, 95% CI: 1.02–2.00, p  = 0.04).The haplotype analysis detected that "ATATCGCC" decreased the risk of cirrhosis developed into liver cancer (OR = 0.69, 95% CI: 0.51–0.92, 95% CI: p  = 0.013); however, "TGAGCGTC" increased the risk of cirrhosis developed into liver cancer (OR = 1.48, 95% CI: 1.04–2.10, p  = 0.027). Meta‐analysis shown that ACYP2 rs1682111 was associated with the risk of cancer (OR = 0.90, 95% CI: 0.78–1.05, p  = 0.02). ACYP2 gene high expression was found to be associated with better OS for all liver patients. Conclusion: Based on this research, we surmised that ACYP2 gene may be involved in the occurrence of liver cancer in Chinese populations. Abstract : Based on this research, we surmised that ACYP2 gene may be involved in the occurrence of liver cancer in Chinese populations.